2021
DOI: 10.1590/s1677-5538.ibju.2020.1007
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of tamsulosin versus tadalafil as medical expulsive therapy on stone expulsion in patients with distal ureteral stones: A randomized double-blind clinical trial

Abstract: Purpose: To compare the effects of tadalafi l, tamsulosin, and placebo as a medical expulsive therapy (MET) for distal ureteral calculi. Materials and Methods: This prospective randomized double-blind clinical trial was conducted on 132 renal colic patients with distal ureteric stones (≤10mm) over a period of 12 months. Patients were randomly divided into three groups. Patients in group A received tamsulosin 0.4mg, in group B received tadalafi l 10mg, and in group C received placebo. Therapy was given for a ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 23 publications
(39 reference statements)
0
7
0
Order By: Relevance
“…Four RCTs that compared tamsulosin with placebo or any other drug except alpha-blockers showed that tamsulosin had a better expulsion rate and time. [3,[17][18][19]. But studies conducted by Puvvada S et al and Kc HB et al showed that tadalafil was better when compared to tamsulosin in terms of expulsion rate and time taken for stone expulsion [20,21].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Four RCTs that compared tamsulosin with placebo or any other drug except alpha-blockers showed that tamsulosin had a better expulsion rate and time. [3,[17][18][19]. But studies conducted by Puvvada S et al and Kc HB et al showed that tadalafil was better when compared to tamsulosin in terms of expulsion rate and time taken for stone expulsion [20,21].…”
Section: Resultsmentioning
confidence: 99%
“…No serious adverse effects were associated with the use of alpha-blockers. Most commonly reported adverse effects included orthostatic hypotension, palpitation, headache, dizziness, backache, abnormal ejaculation, retrograde ejaculation, gastritis, fatigue, nasal congestion, constipation, nausea, diarrhoea, asthenia, increased erection, dry mouth, flushing, muscle cramps, dyspepsia, sexual dysfunction, collapse, vomiting, and hearing problem [2,3,5,6,8,10,12,[17][18][19][20][21][22][23][24]. The detailed results are described in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…Recently have begun to appear the data on the effectiveness of Tadalafil alone and its combination with Tamsulosin on renal calculus clearance after shock wave lithotripsy [ 15 ]. Efficacy of tamsulosin versus tadalafil as medical expulsive therapy on stone expulsion in patients with distal ureteral stones is studying [ 16 ]. Researchers suggested that Tadalafil can dilate ureters promoting the passage of ureteral calculus.…”
Section: Discussionmentioning
confidence: 99%
“…Silodosin has a higher affinity for alpha-1A receptors than tamsulosin, leading to greater selectivity and fewer side effects. Several studies have investigated the efficacy and safety of silodosin in the treatment of ureteral stones and have shown promising results [4]. One metaanalysis of 14 randomized controlled trials involving 1,928 patients compared the efficacy and safety of tamsulosin and silodosin in MET for lower ureteral calculi.…”
Section: Introductionmentioning
confidence: 99%